Christ siemens touraine syndrome: A rare case report - N Retnakumari; Manuja Varghese; V P Kannan (Wolters Kluwer Medknow Publications, 2016)
Christ-Siemens-Touraine (CST) is a rare hereditary disorder of X-linked recessive trait, characterized by abnormal development of two or more structures or tissues of ectodermal origin. The common clinical findings include hypodontia, hypohydrosis, hypotrichosis, and onychodysplasia. Although hypodontia is common, anodontia is a rare feature. Most of the patients are suffering from social rejection and consequent psychological trauma because of the facial dysmorphism and absence of multiple teeth. Oral rehabilitation is of prime importance for such patients. This article presents a case in a 5½-year-old boy presenting with altered manifestations affecting almost all the ectodermal structures like skin, hair, nails, teeth, sebaceous glands, sweat glands, salivary glands, mammary glands, and tear glands. He also had complete anodontia and dry mouth. A multidisciplinary treatment was given to the patient with the collaboration of various health professionals. The child gained confidence and was relieved from the psychological impact following the prosthetic rehabilitation.